Advertisements
Advertisements
Question
Factorise:
3x3 – x2 – 3x + 1
Solution
Let p(x) = 3x3 – x2 – 3x + 1
Constant term of p(x) = 1
Factor of 1 are ±1
By trial, we find that p(1) = 0, so (x – 1) is a factor of p(x)
Now, we see that 3x3 – x2 – 3x + 1
= 3x3 – 3x2 + 2x2 – 2x – x + 1
= 3x2(x – 1) + 2x(x – 1) – 1(x – 1)
= (x – 1)(3x2 + 2x – 1)
Now, (3x2 + 2x – 1) = 3x2 + 3x – x – 1 ...[By splitting middle term]
= 3x(x + 1) – 1(x + 1)
= (x + 1)(3x – 1)
∴ 3x3 – x2 – 3x + 1 = (x – 1)(x + 1)(3x – 1)
APPEARS IN
RELATED QUESTIONS
Identify constant, linear, quadratic and cubic polynomials from the following polynomials:
`f(x)=0`
f(x) = 4x4 − 3x3 − 2x2 + x − 7, g(x) = x − 1
The polynomials ax3 + 3x2 − 3 and 2x3 − 5x + a when divided by (x − 4) leave the remainders R1 and R2 respectively. Find the value of the following case, if R1 = R2.
In each of the following, use factor theorem to find whether polynomial g(x) is a factor of polynomial f(x) or, not: (1−7)
f(x) = x3 − 6x2 + 11x − 6; g(x) = x − 3
If both x + 1 and x − 1 are factors of ax3 + x2 − 2x + b, find the values of a and b.
x3 + 13x2 + 32x + 20
If x + a is a factor of x4 − a2x2 + 3x − 6a, then a =
If (3x − 1)7 = a7x7 + a6x6 + a5x5 +...+ a1x + a0, then a7 + a5 + ...+a1 + a0 =
Factorise the following:
p² – 6p – 16
Factorise:
x3 + x2 – 4x – 4